Report of the Working Group on Vocationalisation of Education and Word Experience January 1968 - Planning Commission (Planning Commission Government of India, 1968)
The Report on Vocationalisation of Education and Work Experience, prepared by the Government of India in 1968, provides a strategic framework to integrate practical skill training into school curricula. Following the Kothari Commission’s recommendations, the initiative emphasizes familiarity with work, dignity of manual labor, and productive engagement across primary to higher secondary levels. The framework includes structured trade education in woodworking, metalwork, electrical repairs, leatherwork, and cookery, supported by Central Work Experience Centres accommodating 440 students in practical sessions. Teacher training, artisan involvement, and phased implementation are recommended to ensure effective skill acquisition. Financial provisions, including capital and recurring expenditures, are outlined to sustain these programs. The report advocates vocational guidance, community relevance, and integration of work experience to cultivate skilled, socially responsible students, bridging the gap between theoretical education and employment readiness.
Government of India Planning Commission New Delhi
Keywords: Vocationalisation; Work Experience; Practical Skills; Curriculum Design; Teacher Training; Central Work Experience Centre; Hands-On Learning; Trade Education; Employment Preparedness; Pilot Projects; Financial Planning; Holistic Development